Describing complex interactions of social-ecological systems for tipping point assessments: an analytical framework - Froese, Rebecca; Andrino, Alberto; Giudice, Renzo; Stuch, Benjamin; Kilian Salas, Simone; Böhner, Jürgen; Boy, Diana; Boy, Jens; Brown, Foster; Díaz García, Elisa; Figueroa, Diana; Frör, Oliver; et al. (Frontiers in Climate, 2023)
1. Humans play an interconnecting role in social-ecological systems (SES), they are part of these systems and act as agents of their destruction and regulation. This study aims to conceptualize potential cascades of tipping dynamics, via (1) the application of a global tipping points (TP) concept to a regional SES, and (2) the systematic assessment of interactions and feedbacks within it by developing a proposed ‘Tipping Multiverse’ framework. 2. We take the southwestern Amazon as an example for tropical regions at large and have identified key underlying sub-systems within the study region: the soil ecosystem, the household livelihood system, the regional social system, and the regional climate system, which are interconnected through a network of feedbacks. We consider these sub-systems as tipping elements (TE) within our analytical framework, which when put under stress, can cross a tipping point (TP), resulting in a qualitative and potentially irreversible change of the respective TE. 3. By systematically assessing linkages and feedbacks within and between TEs, our proposed Tipping Multiverse Framework can provide an entry point for assessing ‘tipping cascades’, which means that the crossing of a TP in one TE may force the tipping of another TE. 4. Policy implications: Such a joint analysis of interactions and potential cascading TPs promotes a better understanding of human-nature interactions and critical linkages within regional SES that may be used for monitoring or intervention purposes, inform policy-making about complex interlinkages and thus enhance the resilience of regional SES.